1996
DOI: 10.1074/jbc.271.50.32330
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Amino Acid Replacements of Glycine 121 on Transmembrane Helix 3 of Rhodopsin

Abstract: Rhodopsin is a member of a family of G protein-coupled receptors with seven transmembrane (TM) helices. In rhodopsin, Gly 121 is a highly conserved amino acid residue near the middle of TM helix 3. TM helix 3 is known to be involved in chromophore-protein interactions and contains the chromophore Schiff base counterion at position 113. We prepared a set of seven single amino acid replacement mutants of rhodopsin at position 121 (G121A, Ser, Thr, Val, Ile, Leu, and Trp) and control mutants with replacements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
107
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(117 citation statements)
references
References 62 publications
8
107
2
Order By: Relevance
“…This agrees with FTIR spectra, which show that the 9-methyl group, 13-methyl group, and ␤-ionone ring affect the early intermediates (32,50,51). In addition, for retinal binding to the opsin apoprotein, the positioning of the ␤-ionone ring and the 9-methyl group have been shown to be crucial (52,53).…”
supporting
confidence: 77%
“…This agrees with FTIR spectra, which show that the 9-methyl group, 13-methyl group, and ␤-ionone ring affect the early intermediates (32,50,51). In addition, for retinal binding to the opsin apoprotein, the positioning of the ␤-ionone ring and the 9-methyl group have been shown to be crucial (52,53).…”
supporting
confidence: 77%
“…Previously, alanine substitution of PheVI:09 in rhodopsin demonstrated that the mutant receptor reconstituted normally with the 11-cis-retinal chromophore but that it displayed decreased ability to light-dependently activate transducin in analogy with the present observations of functional impairment in a number of other 7TM receptors (24,25). Similarly, in the cholecystokinin B receptor, alanine substitution of PheVI:09 resulted in a receptor with retained high affinity agonist binding but impaired signaling (26).…”
Section: Discussionmentioning
confidence: 65%
“…Thus, structural changes in the region near Glu 122 and His 211 are required for proper repositioning of the ␤-ionone ring (27). Previous studies have show a direct interaction between 11-cis-retinal and Gly 121 in rhodopsin TM III (31)(32)(33)(34)(35). The increase in the size of Gly 121 correlated directly with the increasing dark state activity.…”
Section: Discussionmentioning
confidence: 86%